1988
DOI: 10.2190/rhk2-416v-mgxh-hykl
|View full text |Cite
|
Sign up to set email alerts
|

Older People in Disaster: A Comparison of Black and White Victims

Abstract: This research examines differential vulnerability to environmental stressors among white and black elderly and non-elderly disaster victims. The research identifies the determinants of psychosocial recovery for those four demographic groups. A total of 431 families who were victims of a tornado were interviewed for the study. A path model of the determinants of psychosocial recovery is presented, and observations are made regarding intervention strategies for older disaster victims.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 8 publications
2
90
0
3
Order By: Relevance
“…The post-disaster increases on utilization of general practice services and on psychological problems and physical symptoms were comparable in Turkish and in Dutch victims, whereas the Turkish had higher levels than the Dutch prior to and following the disaster. The finding of an equivalent association between experiencing the disaster and health problems between immigrants and indigenous contradicts the conclusions of many studies (Bolin and Klenow 1988;Galea et al 2004;Garrison et al 1995;Lonigan et al 1991;Perilla et al 2002;Drogendijk et al 2003), which demonstrated that ethnic minority groups were more at risk of psychological problems. The question, however, is how to explain this finding?…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The post-disaster increases on utilization of general practice services and on psychological problems and physical symptoms were comparable in Turkish and in Dutch victims, whereas the Turkish had higher levels than the Dutch prior to and following the disaster. The finding of an equivalent association between experiencing the disaster and health problems between immigrants and indigenous contradicts the conclusions of many studies (Bolin and Klenow 1988;Galea et al 2004;Garrison et al 1995;Lonigan et al 1991;Perilla et al 2002;Drogendijk et al 2003), which demonstrated that ethnic minority groups were more at risk of psychological problems. The question, however, is how to explain this finding?…”
Section: Discussionmentioning
confidence: 76%
“…The disaster literature shows that ethnic minority groups have been described with higher rates of post-disaster mental health problems than other groups Bolin and Klenow 1988;Fothergill et al 1999;Galea et al 2004;Garrison et al 1995;La Greca et al 1998;Lonigan et al 1991;Perilla et al 2002). However, these studies did not make use of pre-disaster assessments.…”
Section: Introductionmentioning
confidence: 99%
“…(Wisner et al, 2004: 11). Empirical studies support this, showing that after a disaster, immigrants, single mothers, children, the poor, and ethnic minorities are more affected and receive less help than other groups (Bolin, 1986;Morrow, 1999;Peacock, et al, 1997). Thus groups that have limited economic resources, belong to lower social strata, and live in deprived areas are less resilient to crises and disasters (Barnshaw and Trainor, 2007).…”
Section: Theory and Previous Researchmentioning
confidence: 99%
“…La vulnérabilité des personnes âgées de 65 ans ou plus semble trop souvent ignorée par les autorités gouvernementales et civiles, même si des organismes évaluent les besoins des victimes afin de déterminer Tordre des priorités de la communauté (Aldrich & Benson, 2008;HelpAge International, 1999 (Bolin & Klenow, 1988). Malgré le fait que ce type de clientèle ne se plaigne généralement pas, il a été démontré que pour les personnes âgées de 65 ans ou plus, l'aide venant de l'extérieur n'abonde pas (Fields, 1996;Thomas & Durant, 2011).…”
Section: Les Facteurs Qui Vulnérabilisent Ou Qui Protègent Les Personunclassified